The role of soil processes in δ18O terrestrial climate proxies. Issue 3 (13th March 2014) - Kanner, Lisa C.; Buenning, Nikolaus H.; Stott, Lowell D.; Timmermann, Axel; Noone, David
Abstract A paleoclimate interpretation of a terrestrial hydrologic proxy such as the δ18O of tree cellulose or speleothem calcite may be biased or misinterpreted if the isotopic composition of the soil water from which the proxy originated undergoes isotopic exchange or fractionation. In this study, we use a global isotope‐enabled land surface model to investigate how the δ18O of precipitation may be altered in a soil column due to evaporation and vertical moisture transport. In order to assess how precipitation and evaporation contribute to the soil water isotopic variability, we compare seasonal and interannual changes in simulated xylem water δ18O within a control simulation and in a suite of sensitivity experiments where the effects of precipitation δ18O, water vapor δ18O, and soil water evaporation are independently removed. The simulations, carried out for the period 1979 to 2004, reveal that in semiarid regions, such as the southwest United States, the seasonal cycle in xylem water δ18O is strongly affected by evaporative loss during the dry season and evaporation can also constitute as much as 50% of the interannual δ18O variance. Additional simulations, including soil water tagging experiments, indicate that upward fluxes of soil water occur during drier periods. For soil water δ18O profiles that are isotopically more depleted in 18O at depth, this imparts a low isotopic signature to xylem water δ18O during such dry intervals. Hence, without taking into account vertical moisture transport in the soils, low δ18O years could be misinterpreted as wet conditions (due to decreased evaporative enrichment) when instead drier conditions are equally as likely.